THE EFFECTIVENESS OF ETHANOL EXTRACT OF JAMBLANG LEAVES (Syzygium cumini L.) IN INCREASING HDL LEVELS IN WISTAR RATS MODELS OF METABOLIC SYNDROME - Muthmainah Muthmainah; Ida Nurwati; Selfi Handayani; Dyonisa Nasirochmi Pakha (Jurnal Riset Kesehatan, 2023)
One of the characteristics of metabolic syndrome (MetS) is the low high-density lipoprotein (HDL) levels. Jamblang leaves (Syzygium cumini L.) contain various phytochemicals, which have antihyperglycemic, antihyperlipidemic, and antioxidant properties. This study aims to demonstrate the effectiveness of ethanol extract of jamblang leaves in increasing HDL levels in the Wistar rats model of MetS. A pretest-posttest with a control group design was conducted using 30 male Wistar rats, divided into five groups randomly, with six rats for each group.  Here, KN means normal control group, K- negative control group, and P1, P2, and P3: treatment groups that were administered the 100 mg/kg/day, 150 mg/kg/day, and 200 mg/kg/day of ethanol extract of jamblang leaves for 28 days, respectively. The rat MetS model was developed by administering the high-fat fructose diet and streptozotocin-nicotinamide. The data were analyzed using paired t-test and one-way ANOVA (α=0.05). This study found that extract administration in P2 and P3 increased HDL levels significantly, but not with the P1 group. However, HDL levels in P1 were significantly higher compared to the K- group. Moreover, increasing the dose was significantly followed by higher HDL levels, although the highest dose did not reach the HDL level as in the KN group.